Supporting micro-learning access through the Ujuzi Mobile App: a brokerage deployment model and pilot study for Tanzanian Higher Education Institutions - Ghasia, Mohamed A. (Ghent University, 2024)
Dissertation presented in the fulfilment of the requirements for the Degree of Doctor in Comparative Science of Cultures